Impacts of suicide bereavement on men: a systematic review - Logan, Nina; Krysinska, Karolina; Andriessen, Karl (Frontiers in Public Health, 2024)
Introduction This systematic review examines the impacts of suicide bereavement on men’s psychosocial outcomes relating to suicidality, mental health, substance use, grief, and social functioning. Given the high global incidence of suicide and the substantial number of individuals affected by each suicide, understanding the specific experiences and outcomes for men is crucial, particularly in the context of observed gender differences in suicide rates, grief coping styles and mental health outcomes. Methods Adhering to PRISMA guidelines, this review included peer-reviewed, English-language studies that involved men bereaved by suicide using quantitative, qualitative and mixed-methods designs. Searches were conducted in MEDLINE, Embase, Emcare, PsycINFO, and Scopus. Analysis used narrative synthesis methods due to the heterogeneity of findings. These were categorised based on comparison groups: non-bereaved men, or women bereaved by suicide. Prospero registration: CRD42023437034. Results The review included 35 studies (25 quantitative, 8 qualitative, 2 mixed-methods) published between 1995 and 2023. Compared to non-bereaved men, suicide-bereaved men are more likely to experience adverse psychosocial outcomes included increased suicide mortality, heightened susceptibility to mental health problems such as depression and posttraumatic stress disorder, and challenges in interpersonal relationships and social functioning. The review also identified gender differences in grief responses and coping strategies, with men often exhibiting more pronounced grief reactions and facing unique challenges due to societal expectations and norms regarding masculinity. Discussion The findings of this review underscore the elevated risk of adverse suicide- and mental-health related outcomes for suicide-bereaved men and the need for tailored postvention supports for this cohort. Gender-specific factors, including cultural norms and coping strategies, significantly influence men’s experiences of suicide bereavement. Further qualitative and longitudinal quantitative exploration is needed to enhance understanding and effective support for men bereaved by suicide. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023437034.